A phenomenological investigation of divers` lived experience of imagery - Post, P. G.; Simpson, D.; Young, G.; Parker, J. F. (Journal of Imagery Research in Sport and Physical Activity, 2014)
Phenomenological interviews were conducted with 15 skilled divers (M=29.87 years; SD=8.30), ranging in competitive level from college to Olympic, to explore their lived experience of using imagery. Qualitative analysis of interview data revealed a total of 696 meaning units which were used to produce a final thematic structure consisting of four higher order themes: time and place, perfecting the dive, mentally preparing, and constructing the image. The results suggest that skilled divers` imagery is an active process (i.e., includes different perspectives, speeds, and overt movements) and they use imagery for several purposes (i.e., physical and psychological). Results unique to the present study were divers` manipulations of imagery speed, the incorporation of body movements during their imagery rehearsal to enhance the kinesthetic sensation associated with their desired image, the use of imagery aids to augment their imagery practice, and the use of imagery to focus and avoid distractions during competition. These specific nuances of divers` use of imagery offer several practical applications for sport psychology consultants and coaches interested in implementing imagery interventions with this athlete population.